Infección recurrente por Clostridium difficile en pediatría. Reporte de dos casos y revisión de la literatura (2016)
dence of some bacterial infections such as Clostridium difficile (CD). Despite appropriate treatment, these infections have a high recurrence rate which requires appropriate management and monitoring guidelines. Methodology: This article presents the cases of two pediatric patients who experienced CD reinfection on more than one episode. Patients were treated in Gastroenterology, Hepatology and Nutrition Unit of Gastronutriped in Bogotá, Colombia. In addition, the article provides an update on identification of risk factors, diagnosis and treatment of recurrent CD infections. Conclusions: Cases of CD infections in the pediatric population present a challenge because of their similarity to other infectious processes. When there are bloody stools in a patient with a history of prior use of antibiotics, the infection should be suspected. Reinfection can occur up to 3 months after the initial infection. Management of the first reinfection in mild cases does not require antibiotics, but moderate or severe may be treated with metronidazole if it was used for initial treatment. In cases of a second reinfection, vancomycin should be used. The most appropriate treatment for cases of three or more episodes is still a matter of debate. In recent years, the use of probiotics and fecal microbiota transplantation have shown great benefits in cases of reinfection, though the available evidence is still inconclusive